A new species of the genus Daplasa Moore from China based on morphological and molecular evidence (Lepidoptera: Erebidae: Lymantriinae) - An, Xuan; Da, Wa; Wang, Min; Wang, Houshuai (Zootaxa, 2021)
A new species, Daplasa medoga sp. nov., is described from Tibet, China. The new species can be distinguished morphologically from all other known Daplasa species by its male genitalia with a sagittate uncus and distally broadly crotched valvae. The validity of new species is well supported by the molecular phylogenetic analyses of one mitochondrial gene (COI) and two nuclear genes (EF-1α & RPS5), with a total length of 2,324 bp.